2019
DOI: 10.1159/000503756
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-133a-5p and ROCK2 in Heart in Methamphetamine-Induced Rats and Intervention of Rhynchophylline

Abstract: Introduction: Rhynchophylline, as a traditional Chinese medicine, was used for the treatment of drug addiction. Objective: To investigate miRNAs expression profile in the rat hearts of methamphetamine dependence and the intervention mechanisms of rhynchophylline. Materials and Methods: This study detected the expression profile of miRNAs in the methamphetamine-induced rat hearts by microarray and verified the expression of miR-133a-5P and Rho-associated, coiled-coil containing protein kinase 2 (ROCK2) protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous studies have suggested that ROCK2 performs functional roles in multiple cellular processes, including cell motility, cell adhesion, cell apoptosis, vascular inflammation, and reconstruction (Noma et al., 2006 ). In addition, ROCK2 expression is subject to changes under pathophysiological conditions (Magro et al., 2020 ; Qin et al., 2022 ; Zhou et al., 2020 ). It has been reported that ROCK2 is connected to diverse cardiovascular diseases, including atherosclerosis, hypertension, cardiac hypertrophy, and ischemic stroke (Lee et al., 2014 ; Okamoto et al., 2013 ; Takeda et al., 2019 ; Yamamura et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that ROCK2 performs functional roles in multiple cellular processes, including cell motility, cell adhesion, cell apoptosis, vascular inflammation, and reconstruction (Noma et al., 2006 ). In addition, ROCK2 expression is subject to changes under pathophysiological conditions (Magro et al., 2020 ; Qin et al., 2022 ; Zhou et al., 2020 ). It has been reported that ROCK2 is connected to diverse cardiovascular diseases, including atherosclerosis, hypertension, cardiac hypertrophy, and ischemic stroke (Lee et al., 2014 ; Okamoto et al., 2013 ; Takeda et al., 2019 ; Yamamura et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can be exemplified with the study on EVs-encapsulated miR-29, which has been showed to regulate morphine-mediated neuronal dysfunction by targeting platelet-derived growth factor-B [22]. Moreover, our previous study showed the expressions of some miRNAs were changed in heart in Meth-induced rats, whereas these miRNAs can be reversed by Rhy treatment [23]. It is thus essential to study the roles and mechanisms of action of cardiomyocyte-derived EVs-containing miRNA in Meth dependence and Rhy treatments.…”
Section: Introductionmentioning
confidence: 97%
“…11 MA can also induce Rho-associated protein kinase 2 (ROCK2), which plays an important role in regulating apoptosis of myocardial cells. [12][13][14] To date, however, the mechanism by which MA induces oxidative stress and apoptosis is not clear in the field of drug injury, and further research is needed.…”
Section: Introductionmentioning
confidence: 99%